The implementation of RADEC learning model in thematic learning to increase the concept understanding of electrical phenomenon - Rohmawatiningsih, Wati; Rachman, Indriyani; Yayoi, Kodama (Momentum: Physics Education Journal, 2021)
This research is motivated by the large number of elementary school classrooms that do not offer quality science experiences to students so that it has an impact on students' low understanding of the science concept. The RADEC (Read-Answer-Discuss-Explain And Create) learning model seems suitable for increasing students' understanding of science concepts. This learning model has scientific stages that encourage the cons-truction of students' knowledge. This study aims to analyze the increased understanding of the concept of electrical phenomena through the application of the RADEC learning model. The study involved twenty-eight grade 5 students in the 2019-2020 academic year. Quasi-experimental method with one-group pretest-postest design was used in this study. To find out the understanding of students' concepts about electrical phenomena, tests were carried out before and after the implementation. This study uses descriptive analysis to analyze data collected before and after implementation. From the results of the analysis, it is known that students' understanding of the concept of electrical phenomena after the implementation of the RADEC learning model is higher than before. Thus, it can be concluded that the application of the RADEC learning model can improve students' conceptual understanding of electrical phenomena.